Durable-goods oligopoly with secondary markets: Theory and an empirical application to the automobile market - Susanna Esteban; Matthew Shum (The Johns Hopkins University, Department of Economics, 2001)
We examine the effects of durability on equilibrium producer behavior in the car market In this setting forward-looking producers take into account the effect that their current production decisions have on their current and future profits due to the existence of a secondary market First we construct a dynamic oligopoly model of a vertically-differentiated product market to understand the equilibrium production dynamics which arise from the durability of the goods and their active trade in secondary markets Second we use data from the automobile industry to estimate a tractable linear-quadratic version of this model One result suggests that durability may be a particularly desirable car feature for high-quality car producers since by overproducing today they can exploit durability and the existence of a secondary market to potentially reduce their lower-quality competitors' future production: planned obsolescence appears to be a more profitable strategy for lower-end than higher-end producers
Keywords: 330; Dauerhaftes Konsumgut; Oligopol; Gebrauchtmarkt; Dynamisches Spiel; Theorie